An inhibition of p62/SQSTM1 caused autophagic cell death of several human carcinoma cells. Issue 5 (9th April 2014) - Nihira, Kaito; Miki, Yasuhiro; Ono, Katsuhiko; Suzuki, Takashi; Sasano, Hironobu
<x xml:space="preserve">Abstract</x> p62/SQSTM1 (p62) is a multifunctional protein implicated in several signal transduction pathways and selectively degraded by autophagy, a process for lysosomal degradation of both protein and organelle. p62 was also recently reported to be overexpressed in various malignancies and its inhibition to suppress carcinoma cell proliferation. However, its correlation with autophagy in carcinoma cells has remained largely unknown. Therefore, in this study, we examined the effects of p62 inhibition on the regulation of autophagy and cell survival in p62‐positive carcinoma cells. p62‐silencing dramatically suppressed cell proliferation and induced autophagy in p62 expressing PC9 and A549 cells. Electron microscopical analysis revealed the formation of autophagosomes with multilayer membranes caused by p62‐silencing. p62 silencing‐mediated reduced cell viability was restored by both genomic and pharmacological inhibition of autophagy but not that of apoptosis. These findings were also detected in several types of carcinoma cell lines including adenocarcinomas and squamous cell carcinomas. Results of our present study revealed that an inhibition of p62 resulted in the formation of mis‐regulated autophagosomes with multilayer membranes and an autophagic cell death, and p62 can therefore be an attractive target for the development of anti‐neoplastic agents.